Моделювання теплофізичних процесів водогрійних котлоагрегатів - Тарас, Б. І. (Видавництво Львівської політехніки, 2011)
Done simulation of channel "fuel consumption -temperature water" of boiler КБНГ-2, 5. Analyzed the dynamic characteristics of sections and whole control loop.
Keywords: автоматизація процесів керування; водогрійні котлоагрегати; моделювання